Justin Martyr and Tatian the Syrian in their Roman context - Kirsch-Klingelhöffer, Charlotte (Early Christianity in Rome, 2026)
The following article focuses on two authors - Justin Martyr and Tatian the Syrian - and their "Roman context". I intend to offer an overview from different perspectives in order to understand the (limited) topographical and social information we can gather about the lives of these two ‘apologists’ in the capital of the Roman Empire. After a brief overview of their biographies and the sources available to us (1), the following issues are addressed by showing parallels and differences between these two authors: (2) Is it possible to locate Justin in Rome? (3) What can we learn about Roman topography from Justin’s and Tatian’s writings? (4) How can we understand the social environment of "Christian philosophers" in the city of Rome?
Gesehen am 20.01.2026